THE EFFECT OF SCIENTIFIC APPROACH TO THE SCIENCE PROCESS SKILLS ON GLOBAL WARMING MATERIAL IN VII CLASS - Yustina Hapida; Nurlaeli .; Ayu Dara Kharisma (Al 'Ilmi : Jurnal Pendidikan MIPA, 2016)
The implementation of the 2013 curriculum has emphasized the process of learning with a scientific approach. Scientific approach is highly centered on learners. This study aims to determine the influence of scientific approach to science process in VII class. The research method used quasi-experiment and using non - equivalent control group design. The sample of the study amounted to 74 students. The results showed that the science process skills of learners on the implementation of learning with a scientific approach is better than the control class. Communication skills are the most valuable aspect of science process skills whereas prediction skills are the least valuable aspects of science process skills. Based on the calculation of t test, the science process skill of students showed tarithmetic = 2.630 while t table with α = 5% and dk = 74 - 2 = 72 obtained result 1.670, because tarithmetic > t table . It can be concluded that H0 is rejected and Ha is accepted. This is reinforced by the results of the N-gain test, improving the science process skills of learners in the experimental class of 0.53 while in the control class of 0.32. Based on the results of research can be concluded that the scientific approach affects the skills of students' science processes on the material global warming at VII class. Keywords: scientific approach, science process skills, global warming